(untitled) (Journal of Dhaka Medical College, 2015)
Keloids are common and cause functional and psychological morbidity. A wide variety of treatments, all in current usage, indicate that no treatment has been shown to be markedly superior to the others. This study was done using pulsed dye laser followed by more traditional intralesional steroid injection in the treatment of keloid. The aim of this study was to determine the effectiveness of the PDL in combination with intralesional triamcinolone acetonide (TCA) in the treatment of keloid and to elucidate possible side effects and complications. A prospective clinical trial was done in the Department of Dermatology & Venereology, Combined Military Hospital, Dhaka Cantonment, Dhaka, from December 2013 to February 2014. Adult patients of both sexes (Fitzpatric skin type IV & V) aged between 15 and 50 years with varying degree of keloids were randomly selected for the study. In this single-blinded clinical trial, 50 patients were randomly assigned and was irradiated by 595-nm flashlamp-pumped pulsed-dye laser (PDL, 5-7.5 J/cm2) at the 1st,4th, and 8th weeks and Intralesional steroid was given following PDL. Lesions were assessed for vascularity, pliability, pigmentation and height. The study showed an excellent improvement in nearly all measures, Good to excellent improvements (>76% improvement) were reported by 93% patient. Vancouver scar scale (0-14) decreased from 12.17 to a post treatment value of 3.41which is an excellent achievement. Results were reported by the blinded observer as follows: in vascularity (from 2.7 to 0.61), in pliability (from 3.9 to 1.1), in hyperpigmentation (from 2.4 to 0.92), in height (from 2.87 to 0.78). J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 234-238